Characterising neuropsychological rehabilitation service users for service design. Issue 1 (4th February 2014) - Gracey, Fergus; Malley, Donna; P. Wagner, Adam; Clare, Isabel
Abstract : Purpose: – Needs of people following acquired brain injury vary over their life-course presenting challenges for community services, especially for those with "hidden" neuropsychological needs. Characterisation of subtypes of rehabilitation service user may help improve service design towards optimal targeting of resources. This paper aims to characterise a neuropsychologically complex group of service users. Design/methodology/approach: – Preliminary data from 35 participants accepted for a holistic neuropsychological rehabilitation day programme were subject to cluster analysis using self-ratings of mood, executive function and brain injury symptomatology. Findings: – Analysis identified three clusters significantly differentiated in terms of symptom severity (Cluster 1 least and Cluster 2 most severe), self-esteem (Clusters 2 and 3 low self-esteem) and mood (Cluster 2 more anxious and depressed). The three clusters were then compared on characteristics including age at injury, type of injury, chronicity of problems, presence of pre-injury problems and completion of rehabilitation. Cluster 2 were significantly younger at time of injury, and all had head injury. Research limitations/implications: – Results suggest different subgroups of neuropsychological rehabilitation service user, highlighting the importance of early identification and provision of rehabilitation to prevent deterioration, especially for those injured when young. Implications for design of, and research into, community rehabilitation service design for those with "hidden disability" are considered. Originality/value: – The paper findings suggests that innovative conceptual frameworks for understanding potentially complex longer term outcomes are required to enable development of tools for triaging and efficient allocation of community service resources.